ANALISIS KOMUNIKASI PEMBELAJARAN GURU KELAS DENGAN SISWA KELAS VI DI SEKOLAH DASAR - Abi, Antonius Remigius; Ana, Juli; Tanjung, Darinda Sofia; Tamba, Govindo Roy Frederikus (Universitas Negeri Medan, 2023)
The study was entitled œ Analysis of Class Teacher Learning Communication with Class VI Students SD N 6 Onanrunggu Learning Year 2022/2023. This research was carried out to discover how Class Teacher Learning Communication With Class VI Students. The research method used is a qualitative method with the approach in this study is a case study approach to produce descriptive data in the form of written or oral words from the subject/actors and behaviors that can be observed with the aim of knowing deeply and trying to find the underlying meaning regarding Class Teacher Learning Communication with Students. Learning communication is a reciprocal relationship between teachers (communicator) who deliver messages to students ( comunicant) as recipients of messages through media that accumulate certain effects. The data analysis techniques used in this study are data collection, data reduction, data display and verifiying. Based on the results of the study it can be concluded that in general Class Teacher Learning Communication With Class VI Students SD N 6 Onanrunggu is not yet maximum.